2020
DOI: 10.1371/journal.pone.0242545
|View full text |Cite
|
Sign up to set email alerts
|

Acuities into tolerance mechanisms via different bioassay during Brassicaceae-Alternaria brassicicola interaction and its impact on yield

Abstract: Heavy losses by dark leaf spot disease in oilseed Brassica have incited research towards identifying sources of genetic tolerance against causal pathogen, Alternaria brassicicola. Several morpho-molecular parameters were evaluated to test the performance of field mustard and rapeseed genotypes under artificial inoculation with this pathogen. During Brassica-Alternaria interaction, physio-biochemical defense response was witnessed in tolerant genotypes. Two tolerant genotypes (one for field mustard and one for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…A similar trend of a decreased chlorophyll content has been described during progressive infection of B. oleracea with A. brassicicola [35] and B. juncea infected with A. brassicae [48]. Chlorophyll content decreased in tolerant and susceptible B. napus and B. rapa cultivars to A. brassicicola infection with much stronger degradation in susceptible cultivars [49]. Lowered chl a level accompanied by an extensive production of ROS has been also described in susceptible B. napus infected with Leptosphaeria maculans, which induces yellowish necrotic spots [50].…”
Section: Day Length-dependent Negative Regulation Of Photosynthesissupporting
confidence: 75%
See 1 more Smart Citation
“…A similar trend of a decreased chlorophyll content has been described during progressive infection of B. oleracea with A. brassicicola [35] and B. juncea infected with A. brassicae [48]. Chlorophyll content decreased in tolerant and susceptible B. napus and B. rapa cultivars to A. brassicicola infection with much stronger degradation in susceptible cultivars [49]. Lowered chl a level accompanied by an extensive production of ROS has been also described in susceptible B. napus infected with Leptosphaeria maculans, which induces yellowish necrotic spots [50].…”
Section: Day Length-dependent Negative Regulation Of Photosynthesissupporting
confidence: 75%
“…Carotenoids along with chlorophylls are important photosynthetic pigments that are components of photosystems, they absorb an excess of light, and play a role in photoprotection [51]. In tolerant and susceptible B. napus and B. rapa cultivars, a decrease in the carotenoid levels in response to A. brassicicola has been noted [49]. However, an increase in carotenoid content has been described in resistant B. napus cultivars infected with L. maculans, while in susceptible oilseed cultivars the carotenoid levels decreased [50].…”
Section: Day Length-dependent Negative Regulation Of Photosynthesismentioning
confidence: 99%
“…Contrary to these results, Munir et al. (2020) have described a much higher increase in the CAT activity of B . napus and B .…”
Section: Discussionmentioning
confidence: 62%
“…The results of this study demonstrated that Bacillus velezensis LG14-3 was chemotactic to banana root exudates and that citric acid and glycine in root exudates enhanced the abilities of LG14-3 root colonization and pathogen inhibition. Sustaining chlorophyll content in plants upon pathogen invasion is vital, as it will permit plant cells to continue photosynthesis [54]. Moreover, pot experiments showed that LG14-3 was efficient in increasing the chlorophyll a and chlorophyll b contents of bananas, which may be one of the reasons for the increase in plant height and weight after the LG14-3 application.…”
Section: Discussionmentioning
confidence: 99%